FEATURES OF CORPORATE GOVERNANCE IN ISLAMIC FINANCIAL INSTITUTIONS - E. Khasyanova (Вестник университета)
The article discusses the main principles of Islamic corporate governance. The distinctive characteristics of corporate governance in comparing with western concept are disclosed. The main elements of corporate governance in the context of epistemological approach, corporate objectives, the nature of management and corporate governance are presented.